Speech Acts in GEICO’s Short Stories and Nursery Rhymes Advertisements - Ivana Tehuayo (Institute of Research and Community Outreach - Petra Christian University, 2019)
In this study, the writer analysed the visual and the verbal data from four of GEICO’s 2010 advertisement campaign using speech acts theories. The illocutionary acts that are found in the advertisements are representatives (16), followed by expressives (4), and directives (4). Through the speech acts types and the visuals, GEICO wants to persuade the audiences to emotionally believe in their company and hopefully use their insurance service. From this study, the writer wants to say that through constructing and formulating the right words in literary works adaptation, one can create a powerful promotion tool that will persuade the audiences to do some beneficial future actions for the speaker. Key words: Speech act, nursery rhyme, short story, advertisement, persuasion, emotional connection.